1999
DOI: 10.1016/s0741-5214(99)70345-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective blinded study of the relationship between plasma homocysteine and progression of symptomatic peripheral arterial disease

Abstract: We conclude that elevated plasma homocysteine levels are associated significantly with death, with death from cardiovascular disease, and with the progression of CHD in patients with symptomatic CVD or LED. These results strongly mandate clinical trials of homocysteine-lowering vitamin therapy in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(88 citation statements)
references
References 34 publications
5
79
0
4
Order By: Relevance
“…39 In HHcy, flow-induced constriction of the arterioles may limit tissue blood supply, whereas the impaired of NO release and upregulated synthesis of TXA 2 in the endothelium, together with the simultaneously increased TXA 2 synthesis in platelets, 11,28 can substantially enhance platelet aggregation as well, favoring thrombus formation and leading to occlusive peripheral vascular disease, such as intermittent claudication. 2,3,40 In conclusion, the present study is the first to demonstrate that flow-dependent arteriolar dilation observed under normal healthy conditions is converted to constriction in HHcy rats. The constriction is due to the simultaneously impaired NO and enhanced TXA 2 mediation of arteriolar responses to increases in flow.…”
Section: February 2001supporting
confidence: 50%
See 1 more Smart Citation
“…39 In HHcy, flow-induced constriction of the arterioles may limit tissue blood supply, whereas the impaired of NO release and upregulated synthesis of TXA 2 in the endothelium, together with the simultaneously increased TXA 2 synthesis in platelets, 11,28 can substantially enhance platelet aggregation as well, favoring thrombus formation and leading to occlusive peripheral vascular disease, such as intermittent claudication. 2,3,40 In conclusion, the present study is the first to demonstrate that flow-dependent arteriolar dilation observed under normal healthy conditions is converted to constriction in HHcy rats. The constriction is due to the simultaneously impaired NO and enhanced TXA 2 mediation of arteriolar responses to increases in flow.…”
Section: February 2001supporting
confidence: 50%
“…Key Words: homocysteine Ⅲ arteriole Ⅲ flow-induced response Ⅲ endothelium Ⅲ nitric oxide Ⅲ thromboxane A 2 I ncreasing epidemiological and experimental evidence suggests that an elevated plasma level of homocysteine is associated with the development of peripheral arterial disease. [1][2][3][4][5] Homocysteine is a sulfur-containing amino acid that is formed during the metabolism of the essential amino acid methionine. 4 Plasma homocysteine concentration can be increased through alterations in genetic and nutritional factors, such as various enzyme (cystathione-␤-synthase, methyltetrahydrofolate reductase) abnormalities and deficiency of vitamins (folic acid, cyanocobalamin, pyridoxal phosphate), all of which participate in the metabolism of homocysteine and methionine (for further references, see Lentz et al 4 ).…”
mentioning
confidence: 99%
“…Homocysteine, independent risk factor for arteriosclerosis and specifically coronary artery disease [43,44], has also been shown to increase levels of superoxide anion via the NADPH oxidase pathway [45]. However, it is not clear whether ceramide could be involved in homocysteine biological functions.…”
Section: Homocysteine and Ceramidementioning
confidence: 99%
“…Studies have suggested that elevated Hcy concentrations are associated with an increased rate of stroke, coronary artery disease (CAD), peripheral vascular disease, and deep venous thrombosis. [3][4][5][6] …”
Section: Introductionmentioning
confidence: 99%